Expression of Drosophila FOXO regulates growth and can phenocopy starvation. - Kramer, J.M.; Davidge, J.T.; Lockyer, J.M.; Staveley, B.E. (BMC Developmental Biology, 2003)
Components of the insulin signaling pathway are important regulators of growth. The FOXO (forkhead box, sub-group "O") transcription factors regulate cellular processes under conditions of low levels of insulin signaling. Studies in mammalian cell culture show that activation of FOXO transcription factors causes cell death or cell cycle arrest. The Caenorhabditis elegans homologue of FOXO, Daf-16, is required for the formation of dauer larvae in response to nutritional stress. In addition, FOXO factors have been implicated in stress resistance and longevity.We have identified the Drosophila melanogaster homologue of FOXO (dFOXO), which is conserved in amino acid sequence compared with the mammalian FOXO homologues and Daf-16. Expression of dFOXO during early larval development causes inhibition of larval growth and alterations in feeding behavior. Inhibition of larval growth is reversible upon discontinuation of dFOXO expression. Expression of dFOXO during the third larval instar or at low levels during development leads to the generation of adults that are reduced in size. Analysis of the wings and eyes of these small flies indicates that the reduction in size is due to decreases in cell size and cell number. Overexpression of dFOXO in the developing eye leads to a characteristic phenotype with reductions in cell size and cell number. This phenotype can be rescued by co-expression of upstream insulin signaling components, dPI3K and dAkt, however, this rescue is not seen when FOXO is mutated to a constitutively active form.dFOXO is conserved in both sequence and regulatory mechanisms when compared with other FOXO homologues. The establishment of Drosophila as a model for the study of FOXO transcription factors should prove beneficial to determining the biological role of these signaling molecules. The alterations in larval development seen upon overexpression of dFOXO closely mimic the phenotypic effects of starvation, suggesting a role for dFOXO in the response to nutritional adversity. This work has implications in the understanding of cancer and insulin related disorders, such as diabetes and obesity.